Quality policy agents in Costa Rican higher education (2019)
This paper analyzes the process of formulation and adoption of accreditation as a component of the higher education quality policy in Costa Rica. This is done from a neoinstitutionalist approach, using the Scharpf (1997) model. Public universities are identified as promoters and directive actors, while private universities are regarded as allied actors. Some international organizations and the government are also key actors in the formulation and adoption process. The adoption of the public interest nature of the National System of Accreditation of Higher Education (Sinaes) is carried out via Law N°8256 of the Republic. The belief and perception of the actors fundamentally lies in considering that the quality of higher education is affected by the massification and proliferation of private universities, as well as the ideas of international organizations that propose as an alternative solution the creation of national education systems accreditation and use evaluation tools to ensure quality. To carry out the analysis, it used discourse analysis, in official documents from Conare and the University of Costa Rica are used, as well as articles from the newspaper La Nación.